Exploring Patient Behaviour and Health Literacy in Drug Resistant Tuberculosis Therapy Program - Rokhmah, Dewi; Dessy Raharyani; Mohamad Revaldo Maury (Universitas Airlangga, 2026)
Background: Drug-resistant tuberculosis (MDR/RR-TB) requires a complex treatment regimen, such as BPaL (bedaquiline + pretomanid + linezolid) and BPaLM (with the addition of moxifloxacin), with a shortened duration of 6–9 months and cure rates of ≥90%. This study aimed to analyze the health literacy level of drug-resistant tuberculosis patients at Ngagelrejo Primary Health Center, Surabaya. Methods: The research employed a quantitative cross-sectional approach involving 30 TB-RO patients as respondents. Data were collected using the Health Literacy Questionnaire (HLQ) and analyzed through univariate and bivariate methods using the Chi-Square test. Results: The health literacy level of drug-resistant TB patients at the Ngagelrejo Community Health Center was in the fairly good category and showed a significant correlation with education level. However, there was no significant association between health literacy and age, gender, or medication adherence. Conclusion: These findings confirm that health literacy is a crucial component in managing drug-resistant TB therapy, despite that it does not play a sole role in determining adherence. To improve treatment success, health literacy strategies need to be directed toward a participatory, communicative, and technology-based approach.